F-Type Lectins: A Highly Diversified Family of Fucose-Binding Proteins with a Unique Sequence Motif and Structural Fold, Involved in Self/Non-Self-Recognition - Vasta, Gerardo R.; Amzel, L. Mario; Bianchet, Mario A.; Cammarata, Matteo; Feng, Chiguang; Saito, Keiko (Frontiers in Immunology, 2017)
The F-type lectin (FTL) family is one of the most recent to be identified and structurally characterized. Members of the FTL family are characterized by a fucose recognition domain (F-type lectin domain; FTLD) that displays a novel jellyroll fold ("F-type" fold) and unique carbohydrate- and calcium-binding sequence motifs. This novel lectin family comprises widely distributed proteins exhibiting single, double or greater multiples of the FTLD, either tandemly arrayed or combined with other structurally and functionally distinct domains, yielding lectin subunits of pleiotropic properties even within a single species. Furthermore, the extraordinary variability of FTL sequences (isoforms) that are expressed in a single individual has revealed genetic mechanisms of diversification in ligand recognition that are unique to FTLs. Functions of FTLs in self/non-self recognition include innate immunity, fertilization, microbial adhesion and pathogenesis, among others. In addition, although the F-type fold is distinctive for FTLs, a structure-based search revealed apparently unrelated proteins with minor sequence similarity to FTLs, that displayed the FTLD fold. In general, the phylogenetic analysis of FTLD sequences from viruses to mammals reveals clades that are consistent with the currently accepted taxonomy of extant species. However, the surprisingly discontinuous distribution of FTLDs within each taxonomic category suggests not only an extensive structural/functional diversification of the FTLs along evolutionary lineages, but also that this intriguing lectin family has been subject to frequent gene duplication, secondary loss, lateral transfer, and functional co-option.